Rome and the near Eastern kingdoms and principalities, 44-31 BC: a study of political relations during civil war - Wijlick, Hendrikus A. M. van ca. 20./21. Jh. (Impact of Empire, 2021)
Intro -- Contents -- Preface -- Figures -- A Note on the Maps, Texts and Abbreviations -- Introduction -- 1 The Near East -- 2 Structure -- 3 Sources -- 4 Client Kings -- Part 1 Prelude -- Chapter 1 Pompey's Reorganisation of the Near East, 66-63 BC -- 1.1 The End of the Great Armenian Empire -- 1.2 War in the Caucasus and the Relations with the Parthians -- 1.3 Amisus and the Friendship with Antiochus of Commagene -- 1.4 Amicitia and Societas -- 1.5 The War against Darius the Mede and the Dissolution of the Seleucid Kingdom -- 1.6 Pompey's Dealings with the Emisenoi and His Reorganisation of the Princedom of Chalcis -- 1.7 The Reorganisation of Judaea -- Part 2 -- Section 144-42 BC -- Chapter 2 Parthia -- 2.1 Parthian Support for Cassius -- 2.2 The Embassy of Labienus and the Battle of Philippi -- Chapter 3 Ptolemaic Kingdom -- 3.1 Supporting Dolabella -- 3.2 Recognition for Ptolemy XV Caesarion -- Chapter 4 Judaea -- 4.1 Judaean Support for the Caesarians in Syria -- 4.2 The Imposition of Financial Contributions -- 4.3 Herod's Promotion -- 4.4 Internal Conflicts and Cassius -- Chapter 5 Princedom of Chalcis and the Emisenoi -- 5.1 The Princedom of Chalcis and Caecilius Bassus -- 5.2 Caecilius Bassus and Emisenian Support -- Section 242-31 BC -- Chapter 6 Parthia -- 6.1 The Parthian Invasion of Syria and Asia Minor -- 6.2 Antony's Parthian Campaign -- Chapter 7 Ptolemaic Kingdom -- 7.1 Antony and Cleopatra in Cilicia -- 7.2 The Assassination of Arsinoe and Serapion -- 7.3 The Territorial Grants of 37/36 -- 7.4 The "Donations of Alexandria" in 34 -- Chapter 8 Judaea -- 8.1 The Quest for Antony's Favour -- 8.2 Privileges Restored to Judaeans -- 8.3 Herod and Phasael Made τετράρχαι of Judaea -- 8.4 The Parthian Invasion and Herod's Promotion to the Kingship -- 8.5 Herod's Return to Judaea, Roman Support and the Intervention at Samosata.